Assessing bridge stiffness decline using power spectral density: A case study on Saigon Bridge - Quang Thanh, Nguyen; Ba Tu, Vu; Anh Tuan, Nguyen; Tien Thuy, Nguyen (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2023)
Bridges, especially civil infrastructure, serve a vital role in social activities. A damaged bridge can cause severe consequences such as traffic congestion, economic impacts, and loss of lives. Therefore, it is crucial for infrastructure management communities to detect and assess the condition of damaged bridges to ensure safety. To address this issue, in this study, the authors have put forth a novel set of parameters that can be used to evaluate the reduction in stiffness of spans over time. The stiffness is a critical factor that determines its structural integrity, and it is essential to monitor any changes in this parameter over the lifespan of the bridge. The proposed parameters take into account factors such as the age of the bridge, the material used in its construction, and environmental factors that may contribute to the degradation of the structure. They conducted experiments on a beam structure to evaluate its ability to monitor the reduction in bearing capacity of Saigon Bridge’s spans using these parameters. To analyze the vibration signals from a randomized traffic load model, they utilized the power spectral density. The results of the study suggest a correlation between the frequency of harmonics and the high-frequency regions observed in the power spectral density and the decline in the stiffness of spans.